Informed consent: psychosocial biases - Filiberti, Antonio; Bellotto, Massimo (Medicina e Morale, 1990)
This study aims to analyze the psychological implications of thc physician's request for informed consent from a patient. Particular attention is given to possible psychological and psychosocial biases which can interfere with the communication established between the physician requesting the consent and his patient. Psychological biascs are. for cxample. those regarding the personalities of the people concerned, the physician and the patient; psychosocial biases are, for example, those connected to the culture of the organizations that the physician belongs to, and the fact that the physician may consider his role more within the field or research or more within that of clinical medicine.